The Monetary Policy – Restrictive or Expansive? - Adam Szafarczyk (Contemporary Economics)
The monetary policy plays an important role in macroeconomic policy of government. There is a question concerning type of this policy ñ expansive or restrictive (easy or tidy monetary policy). Unfortunately, we have a lot of criteria. Each of them gives us other answer. So due to equitation of Irving Fisher we have dominantly expansive monetary policy. This same situation exists when we use nominal value of rediscount interest rate of central bank. Opposite result appears when we use real value of this interest rate or level of obligatory reserve. Taking under consideration liquidity on money market we know, that level of interest rate is too high.